Joint pricing and production management: A geometric programming approach with consideration of cubic production cost function - Seyed Jafar Sadjadi; Aghil Hamidi Hesarsorkh; Mehdi Mohammadi; Ali Bonyadi Naeini (Journal of Industrial Engineering International, 2015)
Coordination and harmony between different departments of a company can be an important factor in achieving competitive advantage if the company corrects alignment between strategies of different departments. This paper presents an integrated decision model based on recent advances of geometric programming technique. The demand of a product considers as a power function of factors such as product's price, marketing expenditures, and consumer service expenditures. Furthermore, production cost considers as a cubic power function of outputs. The model will be solved by recent advances in convex optimization tools. Finally, the solution procedure is illustrated by numerical example.
Keywords: 650; Geometric programming; Production management; Cubic cost production function; Jointness